Pengaruh Nilai Tukar, Inflasi dan Pdb Terhadap Ekspor Non Migas Indonesia - Inna Insana; Marliyah Marliyah; Khairina Tambunan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to evaluate the impact of exchange rates and inflation on non-oil and gas exports in Indonesia, both partially and simultaneously. The research approach used is a quantitative approach, using multiple linear regression analysis method. The independent variables in this study include exchange rates (X1), inflation (X2), and GDP (X3), while the dependent variable is non-oil and gas exports. Data was obtained from secondary data sources with a time span of 2019-2022, and data collection techniques involved literature study and documentation. The results showed that partially, the exchange rate had no significant effect on Indonesia's non-oil and gas exports. Partially, inflation has a significant impact on Indonesia's non-oil and gas exports. Partially, GDP has an effect on Indonesia's non-oil and gas exports. The simultaneous test hypothesis shows that the exchange rate, inflation and GDP together significantly affect the dependent variable (non-oil and gas exports).